Buying to Cope With Scarcity During Public Emergencies: A Serial Mediation Model Based on Cognition-Affect Theory - Ma, Xinran; Liao, Jiangqun (Frontiers in Psychology, 2022)
Panic buying is a common phenomenon that occurs during public emergencies and has a significant undesirable impact on society. This research explored the effect of scarcity on panic buying and the role of perceived control and panic in this effect through big data, an online survey and behavior experiments in a real public emergency (i.e., COVID-19), and simulative public emergencies. The findings showed that scarcity aggravates panic buying (Studies 1-3), and this aggravation effect is serially mediated by perceived control and panic (Studies 2-3). Moreover, this serial mediation model is more suitable for public health emergencies (Study 3). These findings enrich the understanding of panic buying and provide important enlightenment for guiding rational public behavior and managing public opinion during public emergencies.